Link + Hud : heroes by a hair - Pumphrey, Jarrett (Pumphrey, Jarrett. Link and Hud, 2023)
Brothers Lincoln and Hudson Dupré go on imaginary adventures that often wreak havoc in the real world and conspire to undermine their newest babysitter.